A Critical Review of the Last 10 Years of Oleogels in Food - Park, Clifford; Maleky, Farnaz (Frontiers in Sustainable Food Systems, 2020)
The field of oleogel research has been active in recent decades, generating numerous oleogels with desirable properties like thermal resistance, texture, and structural stability. Moreover, several food matrices have been formulated with oleogels. In some cases, oleogels in these food products have been shown to resemble textural attributes of products made with conventional hardstock fat, to enhance dietary nutrition, to demonstrate high physical and oxidative stability, and to exhibit a high oil binding capacity. These innovations clearly illustrate the potential of the field of oleogels, but certain drawbacks and a lack of in-depth information in various aspects have delayed its commercialization in the food industry. This review aims to update the current status of the oleogel field and to cover some areas that need to be addressed to make oleogel foods a reality in the near future.